Bioequivalence Study of Morphine Hydrochloride Oral Solution versus Immediate Release Tablets - Geliya Gildeeva; Andrey Belostotsky; Ekaterina Ezhova; Vladimir Yurkov (Journal of Global Pharma Technology, 2019)
Objective: Comparative study of bioequivalence and safety of Morphine Hydrochloride 2 mg/ml oral solution (T) and Morphine Hydrochloride 10 mg immediate release film-coated tablets (R) after single dose administration (1 ampoule 5 ml, 2 mg/ml / 1 tablet 10 mg) by healthy subjects under fasting conditions. Methods: Open-label, single dose, 2-period crossover, randomized design study in 42 healthy subjects under fasting conditions. Test product: Morphine Hydrochloride 2 mg/ml oral solution (FSUE «Moscow Endocrine Plant», Russia) was compared with the reference product Morphine Hydrochloride 10 mg Immediate Release Tablets (FSUE «Moscow Endocrine Plant», Russia) under fasting conditions. The statistical method is testing for Cmax, AUC0-t and AUC0-∞. Bioequivalence study was based upon the 90% confidence interval (90% CI) for the test and reference geometric mean ratio. Bioequivalence was to be assumed if 90% CI fell within the recommended acceptance interval 80%; 125%.Results:Forty-two subjects completed the study. Both Morphine T and Morphine R exhibited peak plasma Morphine concentrations of 13 ng/ml. 90% CIs of the ln-transformed values of Morphine AUC0-t and Cmax were within 80% to 125% range for bioequivalence. The most common adverse events were anemia and headache. These data show that, in these subjects, Morphine T was bioequivalent to Morphine R, a treatment for pain with well-established efficacy and safety profiles.